2015
DOI: 10.5137/1019-5149.jtn.13589-14.1
|View full text |Cite
|
Sign up to set email alerts
|

Herpes zoster brachial plexopathy: direct steroid injection

Abstract: ABSTRACTwhich started 2 weeks after HZ skin eruption affecting to the left C4 and C6 dermatomes. In the patient's history, the pain started with skin lesions and resolved at the end of the second weeks with oral acyclovir therapy. The patient did not define any pain at the admittance and he had no signs of cranial nerve or meningeal involvement. The skin lesions of HZ were extinguished and widely settled to periarticular region of the left shoulder, lateral surface of the left proximal arm and the left upper b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Whitley et al in a randomized placebo-controlled trial concluded that, in localized herpes zoster, combined acyclovir and prednisone therapy can improve quality of life [23]. Direct steroid administration to the brachial plexus is used in few cases with success [24,25]. Pulsed radiofrequency treatment or classic radiofrequency ablations are also tried at the experimental level in treatment of herpes zoster infections [26].…”
Section: Discussionmentioning
confidence: 99%
“…Whitley et al in a randomized placebo-controlled trial concluded that, in localized herpes zoster, combined acyclovir and prednisone therapy can improve quality of life [23]. Direct steroid administration to the brachial plexus is used in few cases with success [24,25]. Pulsed radiofrequency treatment or classic radiofrequency ablations are also tried at the experimental level in treatment of herpes zoster infections [26].…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of C3-C5 motor nerves could lead to diaphragmatic paresis and induce the clinical manifestations, including dyspnea and pulmonary dysfunction (42,43). The affected ganglion segments and possible clinical manifestation are summarized in Table 1 (3,7,28,34,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63).…”
Section: Clinical Characteristics Of Szpmentioning
confidence: 99%
“…Cell-mediated immunity to VZV declines in the elderly or people with low immunity, which triggers VZV reactivation and causes herpes zoster (HZ). HZ usually presents with typically painful skin eruptions and neuropathic sensory symptoms [3] . The virus is propagated along the hematogenous transmission and nerve axonal transport to the central nervous system leading to meningitis, encephalitis, and myelitis [4] .…”
Section: Introductionmentioning
confidence: 99%